COVID-19: COMPARISON OF SITUATIONAL FACTORS BETWEEN HEALTHCARE WORKERS AND NON-HEALTHCARE WORKERS IN EAST MALAYSIA - Cheah, Phee Kheng; Cheah, Phaik Kin; Ongkili, Darlene; Osterrieder , Anne; Poomchaichote , Tassawan; Waithira, Naomi; Mukaka, Mavuto; Cheah, Phaik Yeong (Malaysian Journal of Public Health Medicine, 2021)
COVID-19 is one of the worst global pandemics in the last 20 years caused by Severe Acute Respiratory Syndrome Coronavirus 2. To control the pandemic in Malaysia, on 18th March 2020 the government implemented the Movement Control Order (MCO), a non-pharmaceutical intervention (NPI) under Malaysia’s Prevention and Control of Infectious Diseases Act 1988. Despite a high rate of compliance to the MCO in East Malaysia, a month after its implementation, a new cluster of infections among hospital healthcare workers (HCW) had emerged. This paper reports the early findings of a multinational study involving Malaysia, Thailand, Italy, and the United Kingdom. Our early analysis seeks to understand two main situational factors in the states of Sabah and Sarawak in East Malaysia – testing rates and household composition between HCW and non-healthcare workers (non-HCW). Our results showed that there were higher testing rates and smaller-sized households among HCW when compared to non-HCW workers.